SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-1419
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Elastomeric Tuned Mass Dampers and Particle Dampers

Abstract: This paper presents a study and comparison of two methods commonly used to treat unwanted vibration in vehicles. Laboratory work was done to measure and compare the effectiveness of common designs for practical tuned mass dampers (TMDs) and particle dampers under a wide range of conditions. The relative strength and weaknesses of the two approaches are compared in their abilities to treat vibration in a system due to resonant modes and forced response. The effectiveness of each method is investigated as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this it is seen that particle damping is effective over a range of excitation, but it has poor control if excitation is too high or too low. [12] Yanchen Du done experimental setup on spring-supported fine particle impact damper in which they integrates the effects of elastic deformation and plastic deformation on cantilever beam. In this experiment they found that particle impact damper reduces 80% of the maximum amplitude of cantilever beam.…”
Section: IImentioning
confidence: 99%
“…In this it is seen that particle damping is effective over a range of excitation, but it has poor control if excitation is too high or too low. [12] Yanchen Du done experimental setup on spring-supported fine particle impact damper in which they integrates the effects of elastic deformation and plastic deformation on cantilever beam. In this experiment they found that particle impact damper reduces 80% of the maximum amplitude of cantilever beam.…”
Section: IImentioning
confidence: 99%
“…In literature comparisons of different damping devices with a PD can be found. A TMD was compared to a PD for a SDOFS in [16]. A well structured detailed analysis for various excitation methods was performed in [17].…”
Section: Introductionmentioning
confidence: 99%
“…An elementary analytical model of PID was also developed. The performance comparison between particle dampers and tuned mass dampers was studied by Aubert et al (2003) for an equal mass of dampers. The tuned mass damper was effective in suppressing the vibrations at a particular resonance frequency, whereas particle dampers were better over a wide frequency range.…”
Section: Introductionmentioning
confidence: 99%